Consistency effect in Level-1 visual perspective-taking and cue-validity effect in attentional orienting: Distinguishing the mentalising account from the submentalising account. Issue 1 (2nd January 2021) - Fan, Cong; Susilo, Tirta; Low, Jason
ABSTRACT: Adults are slower to judge the number of dots they can see when an avatar sees a different number of dots. This consistency effect is interpreted as evidence of implicit mentalising – adults track others' visual perspective even when it is task-irrelevant. The submentalising account, however, argues the effect reflects domain-general attentional orienting. In Experiment 1, using a real human face, the consistency effect was elicited for sighted but not eyes-covered faces with head direction, suggesting participants tracked the agent's mental state. Experiment 2 manipulated how much direction cuing (head-front-gaze-averted vs. head-turned-gaze-maintained) was available and measured implicit mentalising (consistency effect) and attentional orienting (cue-validity effect). Neither effect was modulated by directional cue, but the directional cue's dynamic property appeared to be relevant for generation of cue-validity effect as such. Overall, implicit mentalising as revealed in consistency effect cannot be purely reduced to submentalising processes.